2021
DOI: 10.1111/ijcp.14034
|View full text |Cite
|
Sign up to set email alerts
|

Transcutaneous near‐infrared spectroscopy (NIRS) for monitoring kidney and liver allograft perfusion

Abstract: Kidney transplantation (KT) has become the treatment of choice for paediatric end-stage kidney disease. 1 Nevertheless, in comparison to adults, the small calibre of the vessels and the common size-mismatch between donors and recipients can predispose to vascular complications including allograft thrombosis. The latter may affect up to 10% of KTs and account for 35% of allograft losses in the first year. 2 Similar considerations might be made when dealing with liver transplantation (LT). Even in this case, ear… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
1
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 19 publications
0
7
1
1
Order By: Relevance
“…However, we could not find any association between changes in microcirculation (including NIRS) and the presence of IAH or ACS. This is in contrast to other studies outside the pLT setting [ 42 , 43 ] and the results of our own unpublished studies for patients who had not undergone pLT. In pLT, this could be explained by the extraordinary situation of a denervated liver graft, in combination with hyperdynamic circulation, due to cirrhosis before pLT, leading to an increased total liver blood flow after pLT [ 44 ].…”
Section: Discussioncontrasting
confidence: 99%
“…However, we could not find any association between changes in microcirculation (including NIRS) and the presence of IAH or ACS. This is in contrast to other studies outside the pLT setting [ 42 , 43 ] and the results of our own unpublished studies for patients who had not undergone pLT. In pLT, this could be explained by the extraordinary situation of a denervated liver graft, in combination with hyperdynamic circulation, due to cirrhosis before pLT, leading to an increased total liver blood flow after pLT [ 44 ].…”
Section: Discussioncontrasting
confidence: 99%
“…A systematic review of the literature by Ghidini and colleagues identified 5 pertinent articles: 3 studies on kidney allografts and 2 on liver grafts for a total of 55 pediatric patients and 121 adults. 52 For the kidney allografts, NIRS measurements were significantly related to serum creatinine, estimated-glomerular filtration rate, urinary neutrophil gelatinase-associated lipocalin, serum lactate, resistive index assessed by Doppler-ultrasonography, and systolic blood pressure. For the liver allografts, NIRS showed a significant decrease in liver regional oxygenation before vascular complications occurred.…”
Section: Liver Transplantation (Table 2)mentioning
confidence: 91%
“…A 2021 systematic review 36 found that oxygen saturation determined by NIRS may also be useful in liver and kidney transplantation. They analyzed 5 relevant publications: 3 studied graft perfusion in kidney transplantation and 2 referred to liver transplantation.…”
Section: Transplantationmentioning
confidence: 99%